Single crystal ruthenium(II) complex dye based photodiode - Tataroglu, A.; Dayan, O.; Ozdemir, N.; Serbetci, Z.; A-Ghamdi, Ahmed A.; Dere, A.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2016)
The electrical and photoresponse properties of Ruthenium(II) complex dye based on photodiode were analyzed by current, capacitance and conductance measurements performed in a wide illumination intensity and frequency range. It was observed that the reverse current increases with increasing illumination intensity. The results confirm that the photodiode exhibits a photoconducting behavior. Also, the transient photocurrent, photocapacitance and photoconductance of the photodiode were investigated as a function of time. It was observed that the values of these parameters increase after illuminating and reach back to original value after turning off the illumination. In addition, the interface states and series resistance of the photodiode were determined from capacitance/conductance voltage measurements. The value of these parameters decreases with increasing frequency. The obtained experimental results suggest that the photodiode with Ruthenium/Ru(II) complex thin film could be used in various optoelectronic devices and applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Photodiode; Ruthenium/Ru(II) complex; Transient photocurrent